Spontaneous and tetracosactide‐induced anti‐ACTH antibodies in man. (25th June 2015) - Gan, Earn H.; MacArthur, Katie; Mitchell, Anna L.; Joshi, Abhijit; Crock, Patricia; Pearce, Simon H. S.
Summary: Context: During a clinical trial of regular tetracosactide depot injections, four of 13 patients with autoimmune Addison's disease (AAD) developed adverse reactions immediately following tetracosactide injections. We wished to investigate whether these adverse effects could be due to the production of circulating antitetracosactide (ACTH1–24 ) antibodies. Design: Anti‐ACTH binding activity was investigated using immunoblotting and ELISA on sera from participants in the trial ( n = 13; baseline and after tetracosactide exposure), 131 unrelated patients with AAD, 92 patients with Graves' disease (GD), 15 patients with isolated ACTH deficiency and 102 controls. Immunohistochemistry of human pituitary tissue sections was also performed using pooled sera. Results: Bands at approximately 4 and 6 kDa, corresponding to ACTH1–24 and full‐length ACTH1–39, respectively, were found in 10 of 13 (77%) of sera from trial patients exposed to tetracosactide, including all those who had an adverse reaction. This is in contrast with healthy control sera, which showed no binding. The same 10 subjects also showed high levels of binding to tetracosactide by ELISA, along with 21% of patients with AAD, 14% of patients with GD (both P < 0·001 compared to controls) and 1 isolated ACTH deficiency patient (7% of 15). These sera also recognized native ACTH in human pituitary sections. Conclusion: Our study demonstrates that repeated administration of depot tetracosactide can lead to anti‐ACTH1–24 autoreactivity. In addition, a significant number of patients with AAD and GD also had similar, spontaneous, anti‐ACTH reactivity. The presence of these antibodies could mediate some of the adverse effects or explain the well‐described phenomenon of resistance to chronic ACTH therapy.